Longitudinal Changes in Disc and Retinal Lesions Among Highly Myopic Adolescents in Singapore Over a 10-Year Period. Issue 5 (September 2018) - Wong, Yee-Ling; Ding, Yang; Sabanayagam, Charumathi; Wong, Chee-Wai; Verkicharla, Pavan; Ohno-Matsui, Kyoko; Tan, Donald; Yeo, Anna Chwee-Hong; Hoang, Quan V.; Lamoureux, Ecosse; Saw, Seang-Mei
Abstract : Objectives: To examine the progression pattern of disc and retinal lesions in highly myopic Chinese adolescents over a 10-year period in Singapore. Methods: This longitudinal study included Chinese participants who showed high myopia (spherical equivalent [SE] worse than or equal to −5 diopters [D]), no history of refractive surgery, and available fundus photographs at both 2006 (baseline) and 2016 (10-year follow-up) visits. Forty-four adolescents (aged 12–16 years at baseline) who were re-examined later at follow-up were included. Cycloplegic refraction, biometry, and fundus photography were performed at both visits. A trained grader classified myopic macular degeneration (MMD) based on the Meta–pathologic myopia classification and disc lesions from fundus photographs. Choroidal thickness (CT) measurements were performed at 10-year follow-up using swept-source optical coherence tomography. The ocular parameters and lesions were compared between baseline and follow-up. Results: There was a significant worsening of high myopia at follow-up to −7.5±1.8 D (mean SE±SD) in 2016 versus −6.2±1.3 D in 2006; ( P <0.001). The 10-year changes included increased degree of tessellation (26 eyes, 29.5%), development of new tessellated fundus (19 eyes, 21.6%), disc tilt (7 eyes, 8.0%), and expansion of peripapillary atrophy size (33 eyes, 37.5%). Eyes with early-onset tessellation (present at baseline, 48 eyes) showed significantly thinner CT ( P <0.05), compared with eyes with late-onset tessellation (incident at 10-year follow-up, 19 eyes). No cases of MMD were recorded at baseline or 10-year follow-up. Conclusions: Although there was no incident MMD, the retinal and disc lesions worsened over the follow-up period. Early-onset fundus tessellation was associated with thinner CT.